2021
DOI: 10.1101/2021.02.03.21251065
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of systemic corticosteroids on hospitalized patients with COVID-19: January 2021 Meta-analysis of randomized controlled trials

Abstract: Background: The COVID-19 pandemic has stimulated worldwide investigation into a myriad of potential therapeutic agents, including corticosteroids. The first RCT reporting results on the impact of systemic corticosteroids on COVID-19 in a peer reviewed journal was the RECOVERY trial published in July, 2020. The RECOVERY trial showed a reduced risk of 28-day mortality in patients who received oral or intravenous dexamethasone for 10 days. This study is a meta-analysis of peer reviewed RCTs aims to estimate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…[301] Several meta-analyses indicated that corticosteroids remain effective and safe among severely ill COVID-19 patients, but not among all hospitalized COVID-19 patients. [302][303][304] Accordingly, the WHO guidelines recommend corticosteroid administration for patients with severe COVID-19 or those critically ill with the disease, but not for patients with non-severe COVID-19. [305] A recent study from Wuhan, China, assessed the effect of lowdose aspirin on COVID-19 patients who also had CAD.…”
Section: Sars-cov-2 Infection Of Cardiomyocytes Ecs and Pericytesmentioning
confidence: 99%
“…[301] Several meta-analyses indicated that corticosteroids remain effective and safe among severely ill COVID-19 patients, but not among all hospitalized COVID-19 patients. [302][303][304] Accordingly, the WHO guidelines recommend corticosteroid administration for patients with severe COVID-19 or those critically ill with the disease, but not for patients with non-severe COVID-19. [305] A recent study from Wuhan, China, assessed the effect of lowdose aspirin on COVID-19 patients who also had CAD.…”
Section: Sars-cov-2 Infection Of Cardiomyocytes Ecs and Pericytesmentioning
confidence: 99%
“…Corticosteroid drug has been a subject of various studies, including Recovery which validated its efficacy and brought excellent news [12]. Dexamethasone cannot treat COVID-19, but as has been mentioned, it effectively reduces the massive inflammation that develops in this disease and causes many deaths [13,14]. WHO issues guidelines on the treatment of various diseases.…”
Section: Drug Therapy Of Covid-19 Adverse Effects Of Drugsmentioning
confidence: 99%
“…It is cheap, available, effective and can save many lives. Guidelines recommend using intravenous or tablet form of the corticosteroid therapy with Dexamethasone in patients with a severe course of the disease [13,14]. Prevention of complications is always better than their later management.…”
Section: Drug Therapy Of Covid-19 Adverse Effects Of Drugsmentioning
confidence: 99%
See 1 more Smart Citation